Rafflesia patma Blume in Pananjung Pangandaran Nature Reserve, West Java: Population Structure, Distribution Patterns, and Environmental Influences - Bahana Aditya Adnan; Suwarno Hadisusanto; Purnomo Purnomo (Journal of Tropical Biodiversity and Biotechnology, 2021)
Rafflesia patma is an endemic plant of Pangandaran, West Java which is protected because of its rare status. The purpose of this research is to study the population structure, distribution patterns, and the effect of the physical environment of abundance R. patma in Pananjung Pangandaran Nature Reserve, West Java. The method used in this research was a survey method with a purposive sampling technique. Sampling was conducted using quadrat plots. The population pattern distribution was defined by a standardized Morisita index, and the analysis of abiotic environmental factors was determined by Principal Component Analysis (PCA) using PAST3. The results showed that there were 114 R. patma individuals scattered in several research areas in Pananjung Pangandaran Nature Reserve, they were Gua Parat (3 individuals), Cilegon (13 individuals), Pasir Putih (12 individuals), Badeto (48 individuals), and Curug Leutik (38 individuals). The distribution pattern of R. patma in Pananjung Pangandaran Nature Reserve was clustered with the Morisita index value (Id) > 1. Based on the PCA analysis, results that support the classification of the cluster analysis were obtained. Based on four abiotic environmental conditions analyzed, the most dominant character in influencing the distribution patterns and population structure of R. patma is light intensity.